Identification of virulence genes from non-typeable haemophilus influenzae isolates recovered from pneumonia cases and community controls - Boitshoko Mahlangu, Boitshoko (My University, 2020)
Non-typeable Haemophilus influenzae (NTHi) causes severe upper (URTI) and lower respiratory tract infections (LRTI). Characterising virulence factors of NTHi associated with LRTI, could contribute to identifying potential vaccine epitopes. Our objective was to characterise the prevalence of select NTHi putative virulence factor genes in cultured strains obtained from induced sputum samples of children hospitalised with pneumonia compared to NTHi strains colonising the nasopharynx (NP) of otherwise healthy age group matched community controls (including children with URTI). NTHi samples were collected as part of the Pneumonia Etiology Research for Child Health study conducted between 2011 and 2013 and retrospectively analysed. Cases were defined as children aged 1-59 months hospitalised with World Health Organisation defined severe or very severe pneumonia, and controls were children living within the same study catchment area as the cases without signs and symptoms of severe or very severe pneumonia. H. influenzae isolates underwent standard microbiological tests and were classified as NTHi by PCR using the bexB assay. Additionally, a novel high-throughput genotyping assay was developed and optimised (BioMark-HD system) in order to detect twelve NTHi putative virulence factors. Overall, the study included 113 and 298 NTHi isolates from cases and controls, respectively. NTHi cases were younger than controls (10.1 months vs. 14.2 months; P=0.021) and out of the 12 analysed genes for NTHi proteins, two were significantly higher in cases than controls; i.e. hmwC (58% vs. 39%; P=0.002) and hmw2A (18% vs. 5%; P<0.001). We identified two combinations of genes that were more common in cases than controls, namely hmwC+/infA+/hmw2A+/tehB+/lic2C+ and hmwC+/infA+/hmw2A-/tehB+/lic2C+. The potential of hmwC and hmw2A with or without other putative virulence proteins of NTHi warrant further investigation as potential vaccine targets for the prevention of severe pneumonia due to NTHi.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020